Call to Action: The Need for Adverse Drug Event (ADE) Standardization and Codification Through Improved ADE Definitions, Documentation and Mapping, as well as More Refined Medication Definitions - McCue, John; C. Love, Raymond; David Butler, C. (Journal of Medical Informatics and Decision Making, 2025)
Information on adverse drug event (ADE) assessment and prevention within Electronic Health Records (EHRs) is difficult for clinicians to use and produces wide-ranging results. Challenges include inconsistent ADE and drug product definition and documentation, workflows, terminology standardization, interoperability, and clinical decision support (CDS) to inform clinical decision-making within EHRs. These factors contribute to care issues for clinicians, such as alert fatigue and provider burden for clinicians and medical errors, patient harm, and even death for patients. Clinicians play the primary role in documenting, reviewing, detecting, and preventing ADEs within EHRs. It is essential that clinicians, clinical informaticists, nursing informaticists, pharmacy informaticists, and the health informatics profession understand the current electronic ADE paradigm to advocate for improved detection and prevention of ADEs within EHRs.
Keywords: drug; adverse drug event; allergy; intolerance; patient history; healthcare standardization; clinician; informatics